Animal Fasciolosis in North of Iran - A Eslami; SH Hosseini; B Meshgi (Tehran University of Medical Sciences, 2009)
Background: Fasciolosis is a well known parasitic disease of animals with public health importance. In Rasht and Bandar-Anzali, in Gilan Province, where experienced two large human fasciolosis outbreaks, no update information is available on animal fasciolosis. Paucity of information on animal fasciolosis in these regions and its possible impacts on human fasciolosis called us for carrying out this study. Methods: During 2005, coprologic surveys using flotation method were applied to fecal samples of 156 stray cattle, 171 calves, 178 sheep, 85 buffaloes, 79 horses and 10 samples from 10 different preserved animal manure collections to detect Fasciola egg. Results: Fecal samples of 32 % of sheep, 32.1% of cattle, 0% of calves, 17% of buffaloes, 50% of horses and 100% of animal manure samples harbored Fasciola egg. The mean intensity of Fasciola egg per gram of feces (EPG) was low (0-13). Conclusion: Fasciolosis was very prevalent among animals in studied regions. Because sheep breeding is not a common practice in Rasht and Bandar -Anzali and horse population is low, cattle and to a lesser extent buffalo were the predominant reservoir hosts of infection. Regular treatment of all animals with an effective flukicide and sanitation of animal manure through its preservation for two month should be applied in order to reduce the level of infection in animals, water, wild and cultivated vegetables and consequently human beings.